Pengaruh Pemberian Ekstrak Daun Sirsak terhadap Kadar SGPT dan SGOT Tikus yang Di Induksi Obat Anti Tuberkulosis Isoniazid dan Rifampisin - Napitupulu, Runggu Retno J.; Siregar, Astrid Yemima; Ompusunggu, Henny Erina Saurmauli (Universitas HKBP Nommensen, 2023)
Background: The use of the antituberculosis drugs isoniazid and rifampin triggers hepatotoxicity. Soursop leaves have hepatoprotective effect because they contain antioxidant compounds that can help inhibit and prevent oxidative damage to the liver. This study aims to determine the effect of soursop leaf extract on SGPT and SGOT levels in rats induced by isoniazid and rifampicin.Methods: This experimental laboratory study used the post-test-only control group design. This study used 25 wistar rats divided into five groups and given a 14-day treatment. Group 1 (negative control) was assigned isoniazidand rifampicin without administering soursop leaf extract. Group 2 (positive control) was given isoniazid and rifampicin by administering hepatoprotector compound. Group 3, 4, and 5 were given isoniazid and rifampicin for 1 hour, and continued with the administration of soursop leaf extract with a dose of 36 mg/day, 72 mg/day, and144 mg/day respectively. The dose of the isoniazid used was 189 mg/day, while the rifampicin dose was 252mg/day. Rat termination was carried out on the 15th day. Blood samples to measure SGPT and SGOT levels were taken through intracardial.Results: The results showed that there was a significant difference in SGPT and SGOT levels between the treatment group and negative control at doses of 72 mg/kg body weight/day and 144 mg/kg body weight/day. There was no significant difference between SGPT levels in the treatment group of dose of 144 mg/kg/day and the positive control group. There were significant differences in the SGOT levels of the treatment groups and the positive control group.Conclusion: Administration of soursop leaf extract can lower SGPT and SGOT levels in rat induced with isoniazid and rifampicin. The hepatoprotective effect of soursop leaves was obtained at a dose of 144 mg/kg body weight/day. Keywords: soursop leaf, isoniazid, rifampicin, SGPT, SGOT